2013
DOI: 10.1002/jgrd.50472
|View full text |Cite
|
Sign up to set email alerts
|

Trends in ozone, its precursors, and related secondary oxidation products in Los Angeles, California: A synthesis of measurements from 1960 to 2010

Abstract: [1] Decreases in ozone (O 3 ) observed in California's South Coast Air Basin (SoCAB) over the past five decades have resulted from decreases in local emissions of its precursors, nitrogen oxides (NO x = NO + NO 2 ) and volatile organic compounds (VOCs). Ozone precursors have been characterized in the SoCAB with measurements dating back to 1960. Here we compile an extensive historical data set using measurements in the SoCAB between 1960 and 2010. Faster rates of decrease have occurred in abundances of VOCs (À7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
120
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 93 publications
4
120
2
1
Order By: Relevance
“…Isoprene accounts for the highest OH reactivity especially during the daytime. This analysis is consistent with reports from other suburban observations from East Asian megacities such as Beijing (Ran et al, 2011) and the Pearl River Delta region (Lou et al, 2010) in China and the Kinki region in Japan (Bao et al, 2010).…”
Section: Observational Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Isoprene accounts for the highest OH reactivity especially during the daytime. This analysis is consistent with reports from other suburban observations from East Asian megacities such as Beijing (Ran et al, 2011) and the Pearl River Delta region (Lou et al, 2010) in China and the Kinki region in Japan (Bao et al, 2010).…”
Section: Observational Resultssupporting
confidence: 92%
“…Despite the strong anthropogenic pollutant emissions in East Asia (China, Japan, and South Korea), recent research has shown that isoprene accounts for a major OH chemical sink in suburban areas near Beijing (Ran et al, 2011), the Pearl River Delta region , Taipei (Chang et al, 2014), and Seoul (Kim et al, 2013b;Kim et al, 2013). Consequently, modeling studies also clearly show that isoprene contributes significantly to ozone formation in Asian megacity regions.…”
mentioning
confidence: 99%
“…Model evaluation is confounded by the lack of source information in direct ozone measurements. While co-located measurements of additional species can provide information for source attribution, in most national, longterm networks, only surface ozone measurements are available (with only a couple studies now documenting long-term precursor measurements in North America; see Pollack et al, 2013;Hassler et al, 2016). Progress in model evaluation for such episodes is anticipated with availability of multiple chemical measurements, such as occurs during field campaigns and perhaps in the future from space-based platforms.…”
Section: State Of Knowledgementioning
confidence: 99%
“…Jungfraujoch, Zugspitze, Mace Head) and North America excluding western US rural sites (e.g. US Pacific, Lassen Volcanic National Park; Lefohn et al, 2010;Cui et al, 2011;Parrish et al, 2012;Pollack et al, 2013;Lin et al, 2017), due to a decrease in the emissions of O 3 precursors since the early 1990s (Cui et al, 2011;Derwent et al, 2013). In contrast, the O 3 levels in East Asia increased at a rate of 1.0 ppbv yr −1 from 1998 to 2006, based on measurements at Mt Happo, Japan (Parrish et al, 2012;Tanimoto, 2009).…”
Section: Introductionmentioning
confidence: 99%